Exploration of indigenous copper and dye-resistant bacteria isolated from Citarum River, West Java, Indonesia - WAHYU IRAWATI; DWI NINGSIH SUSILOWATI; INDAH SOFIANA; VALENTINE LINDARTO; REINHARD PINONTOAN; TRIWIBOWO YUWONO (Society for Indonesian Biodiversity, 2023)
Abstract. Irawati W, Susilowati DN, Sofiana I, Lindarto V, Pinontoan R, Yuwono T. 2023. Exploration of indigenous copper and dye-resistant bacteria isolated from Citarum River, West Java, Indonesia. Biodiversitas 24: 1215-1223. Bacterial bioremediation utilizing indigenous bacteria has been reported as an effective, economical, and eco-friendly solution to marine contamination. However, study on the use of dye and copper-resistant bacteria has not been done much. The study aimed to isolate copper and dye-resistant bacteria, determining copper and dye resistance and decolorization abilities. Copper and dye-resistant bacteria were isolated from the Citarum River, West Java, Indonesia. Bacterial isolates were identified based on 16S rDNA gene analysis. Copper resistance was determined by measuring the minimum inhibitory concentration (MIC) of CuSO4. Dye resistance was observed by growing the bacterial isolates on a medium containing 100-500 ppm of various dyes. The dye decolorization was analyzed by monitoring the absorbance of each dye using a spectrophotometer. Fifty-four of copper indigenous resistant bacteria have been isolated. Nine bacterial isolates that showed high resistance to copper and dye with the MIC of 11 mM CuSO4 were identified as Siccibacter colletis, Acinetobacter baumannii, Lysinibacillus fusiformis, Bacillus cereus, and Escherichia coli. The highest multi-resistant bacterium was Bacillus cereus CTR 200 3.2 with decolorization rates of 93.04%, 61.9%, and 87.43% on 100 ppm methylene blue, malachite green, and basic fuchsine dye, respectively. However, adding 5 mM CuSO4 reduced those decolorization rates to 39.39%, 10.48%, and 7.39%, respectively.